Idiopathic Central Precocious Puberty Associated with 11 Mb De Novo Distal Deletion of the Chromosome 9 Short Arm - Mariangela Cisternino; Erika Della Mina; Laura Losa; Alexandra Madè; Giulia Rossetti; Lorenzo Andrea Bassi; Giovanni Pieri; Baran Bayindir; Jole Messa; Orsetta Zuffardi; Roberto Ciccone (Case Reports in Genetics)
We report a girl with a de novo distal deletion of 9p affected by idiopathic central precocious puberty and intellectual disability. Genome-wide array-CGH revealed a terminal deletion of about 11 Mb, allowing to define her karyotype as 46; XX, del(9)(p23-pter). To our knowledge, this is the second reported case of precocious puberty associated with 9p distal deletion. A third case associates precocious puberty with a more proximal 9p deletion del(9)(p12p13,3). In our case, more than 40 genes were encompassed in the deleted region, among which, DMRT1 which is gonad-specific and has a sexually dimorphic expression pattern and ERMP1 which is required in rats for the organization of somatic cells and oocytes into discrete follicular structures. Although we cannot exclude that precocious puberty in our del(9p) patient is a coincidental finding, the report of the other two patients with 9p deletions and precocious puberty indeed suggests a causative relationship.